The Role of Internal Audit in Reducing the Risks of The Automated Clearing House (ACH) In Iraqi Banks: دراسة استطلاعية لعينة من العاملين في بعض الوحدات الاقتصادية المدرجة في سوق العراق للأوراق المالية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the Risks resulting from the application of the Automated Clearing House (ACH) and Audit them by an internal party in the Bank and take the necessary measures to reduce them or reduce them to an acceptable level, and to provide more secure and efficient services and to attract the largest possible number of customers and encourage them to open current accounts and benefit from them. From the sukuk service, and to achieve the research objectives, the researcher prepared a questionnaire form according to a five-point Likert scale to demonstrate the role of Internal Audit in reducing and eliminating the Risks of the Automated Clearing House (ACH) or reducing them to an acceptable or controllable level with the aim of increasing its efficiency and then increasing confidence in the services. Electronic banking, The Researcher reached a set of conclusions, the most important of which is that the Automated Clearing House (ACH) has a role in reducing the Risks of fraud and forgery of instruments, because magnetic electronic instruments have secure specifications that are difficult to manipulate, in addition to providing high quality in payment and collection services Electronic and the speed of money circulation and transfer between banks, The Researcher presented a set of recommendations, the most important of which is working on making updates to the Automated Clearing House (ACH) to include dealing with the Automated Clearing House (ACH) in Banks of the outside world and in various international currencies, as well as transactions in local Banks that are carried out through this system.